In The Name of “Like This”: The Appropriation of Artwork In Digital Age - Pangeran Putra Perkasa Alam Nasution; Mochammad Wahyu Ghani (IJCAS (International Journal of Creative and Arts Studies), 2019)
The rapidly growing and massive information age in digital media platforms has created and introduced cultural ramifications on various aspects of human life.The ongoing era of globalization of the twentieth century has fuel the capabilityin digitizing and manipulating information during traffic. Cultural growth in thenew age includes: ―cultural preservation as the main ingredient of the ordinary‖;the proliferation of electronic visual images; and the construction of amultifaceted and the individual identity or social imaginary. The artworkcurrently is glorifying so many appropriations practices. All the art creations i nthe code of conduct are suitable for one aspiration, and that is the digital aestheticmarket. It is now customary to gather on the variety of artistic creations fromdifferent cultures that are appropriated as new and authentic artwork. Thus, thisarticle discusses the appropriation for the artwork in the rise of the digital mediaplatform era. This paper is an anthropological study that refers to the interpretivereflexive paradigm as the analysis of path-work. Digital media is the unit of analysis in this study.